2022
DOI: 10.3389/fcimb.2022.919346
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the trajectories of SARS-CoV-2 variants of concern between December 2020 and September 2021 in the Canary Islands (Spain)

Abstract: Several variants of concern (VOCs) explain most of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) epidemic waves in Europe. We aimed to dissect the spread of the SARS-CoV-2 VOCs in the Canary Islands (Spain) between December 2020 and September 2021 at a micro-geographical level. We sequenced the viral genome of 8,224 respiratory samples collected in the archipelago. We observed that Alpha (B.1.1.7) and Delta (B.1.617.2 and sublineages) were ubiquitously present in the islands, while Beta (B.1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(24 reference statements)
0
3
0
Order By: Relevance
“…Only those sequences that had an assigned lineage and a percentage of Ns < 10% were categorized as having a “good” or “median” QC and were used for the analysis. Sequences collected up to the 27th of September 2021 are part of previous studies [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Only those sequences that had an assigned lineage and a percentage of Ns < 10% were categorized as having a “good” or “median” QC and were used for the analysis. Sequences collected up to the 27th of September 2021 are part of previous studies [ 5 , 6 ].…”
Section: Methodsmentioning
confidence: 99%
“…More recent studies have shown that BA.4/BA.5 infections are characterized by increased immune evasion compared to BA.1/BA.2 and Delta (B.1.617.2 and sublineages), despite no differences in disease severity have been found between these lineages [ 4 ]. We have previously shown that Delta and its sublineages were associated with higher 28-day mortality than Alpha (B.1.1.7) in hospitalized patients from the Canary Islands region (Spain) [ 5 , 6 ]. By expanding the dataset of viral genome sequences obtained in the region, here we first compared the reinfection rates of circulating variants in a period from December 2020 to July 2022.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in other island communities have reported importation bottlenecks that result in the delayed entry of otherwise common variants. This, for example, resulted in unique variant profiles in the Canary Islands despite strong ties with continental Spain ( Ciuffreda et al, 2022 ) and the island of Ilhabela despite strong ties with continental Sao Paolo (Brazil) ( Viala et al, 2022 ). It may therefore be that Alpha was not imported sufficiently frequently for it to become a dominant variant, or it may be that imported Alpha variants did not possess a sufficient selective advantage to outcompete others in a population where Beta variant circulation was already dominant.…”
Section: Resultsmentioning
confidence: 99%